1994
DOI: 10.1093/ptj/74.7.647
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in Weight-Transfer Capabilities in Adults With Hemiparesis

Abstract: A classification scheme that can distinguish between four categories of bipedal to single-limb stance transitions has been established. Issues concerning clinical assumptions pertaining to the relationship between static and dynamic motor dysfunction in adults with hemiparesis are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
56
0
4

Year Published

1996
1996
2016
2016

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(63 citation statements)
references
References 16 publications
3
56
0
4
Order By: Relevance
“…Using these novel objective analytical methods to evaluate weight transfer will help to provide the needed clinical evidence to incorporate new assessment techniques when selecting the most effective orthotic interventions to efficiently maximize functional recovery and create an improved standard of care for individuals with hemiplegia secondary to stroke. 36 A potential limitation of the current study is that the inclusion and exclusion criteria of the study may have created a sample of stroke patients that were higher functioning, especially because they were able to walk twenty-five feet without their AFO. 37,38 However, research has found that patients who receive an AFO on entry to or discharge from rehabilitation are more functionally impaired than patients who do not receive an AFO.…”
Section: Discussionmentioning
confidence: 98%
“…Using these novel objective analytical methods to evaluate weight transfer will help to provide the needed clinical evidence to incorporate new assessment techniques when selecting the most effective orthotic interventions to efficiently maximize functional recovery and create an improved standard of care for individuals with hemiplegia secondary to stroke. 36 A potential limitation of the current study is that the inclusion and exclusion criteria of the study may have created a sample of stroke patients that were higher functioning, especially because they were able to walk twenty-five feet without their AFO. 37,38 However, research has found that patients who receive an AFO on entry to or discharge from rehabilitation are more functionally impaired than patients who do not receive an AFO.…”
Section: Discussionmentioning
confidence: 98%
“…Studies have reported high within session reliability (consecutive trials) for forward and lateral weight-shifting in persons with stroke, 13 good within session reliability (consecutive trials) for the body centre of mass displacement when transferring weight laterally into a single leg posture in persons with stroke, 27 and good test-retest reliability measured over two separate days for the vertical ground reaction force for healthy adults when rising from a chair. 8 Our study is the first to assess the reliability of weight-bearing abilities over different days in persons with chronic stroke.…”
Section: Reliability Of the Weight-bearing Abilitymentioning
confidence: 99%
“…Among the lower-extremity problems that most hemiplegia patients experience, decrease of proprioceptive sense and muscle strength in the damaged joints lead to asymmetry of the lower extremity [1,2]. Decreased sensory makes it difficult to support weight on the affected side and causes asymmetric weight bearing on both lower extremity [3]. Also, in quiet standing, postural sway occurs more severely because of decreased stability of the affected leg compared with the unaffected leg [4].…”
Section: Introductionmentioning
confidence: 99%